LEGAL EFFECT OF THE CONCURRENT POSITION OF NOTARY AS THE REGIONAL PEOPLE'S REPRESENTATIVE COUNCIL (DPRD) BASED ON THE LAW ON THE POSITION OF NOTARY - Fariz Risang Ahmad; Mohamad Fajri Mekka Putra (Faculty of Law, Universitas Pekalongan, 2021)
Notaries are general officials authorized to do authentic deeds; notaries must comply with laws and regulations and professional codes of ethics. One form of action that deviates from the provisions of rules and regulations and professional codes of ethics is concurrent positions, namely as the Regional People's Representative Council (DPRD). The purpose of the research in this study is to analyze the legal consequences of the concurrent position of a Notary as a DPRD based on the Notary Position Law. This research was carried out using the Normative Juridical method. The normative Juridical Method is a legal research method aiming to gain knowledge about a legal event. The results of the study can be concluded that the Notary Position Law does not regulate the legal consequences of the concurrent position of a Notary as a DPRD. DPRD is not a State Official. As a result of the legal consequences, notaries who concurrently serve as DPRD are regulated by UUMD3, which expressly explains that the DPRD is prohibited from together doing as a Notary. Notaries who together do as DPRD will be subject to sanctions in the form of dismissal as members of the DPRD.